The role of carcinoembryonic antigen-related cell adhesion molecule 1 in cancer - Götz, Lisa; Rueckschloss, Uwe; Balk, Gözde; Pfeiffer, Verena; Ergün, Süleyman; Kleefeldt, Florian (Frontiers in Immunology, 2023)
The Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), also known as CD66a, is a member of the immunoglobulin superfamily. CEACAM1 was shown to be a prognostic marker in patients suffering from cancer. In this review, we summarize pre-clinical and clinical evidence linking CEACAM1 to tumorigenicity and cancer progression. Furthermore, we discuss potential CEACAM1-based mechanisms that may affect cancer biology